Italy : Financial Sector Assessment Program; Detailed Assessment of Implementation of the IOSCO Objectives and Principles of Securities Regulation. (IMF Staff Country Reports; Country Report ;, 2006)
This paper discusses the Financial Sector Assessment Program focusing on Detailed Assessment of Implementation of the International Organization of Securities Commission (IOSCO) Objectives and Principles of Securities Regulation for Italy. The IOSCO Principles list a number of preconditions to effective securities regulation. These include the appropriateness of legal, tax, and accounting framework within which the securities market operates, the effectiveness of procedures for the efficient resolution of problems in the securities market, and the soundness of macroeconomic policies. These preconditions appear to be in place in Italy.